Matrix solid-phase dispersion extraction method for HPLC determination of flavonoids from buckwheat sprouts. (November 2020) - Mansur, Ahmad Rois; Kim, Kwan Joong; Kim, Dan-Bi; Yoo, Miyoung; Jang, Hae Won; Kim, Dae-Ok; Nam, Tae Gyu
Abstract: Herein, we report the development of a matrix solid-phase dispersion (MSPD) extraction method for determining flavonoids (orientin, isoorientin, vitexin, isovitexin, quercetin-3- O -robinobioside, and rutin) from common buckwheat sprouts (CBS) and Tartary buckwheat sprouts (TBS) by high-performance liquid chromatography (HPLC-PDA). Key parameters, including sorbent type, sorbent-to-sample ratio, extraction solvent (type, concentration, and volume), and extraction time were optimized. The optimized MSPD extraction conditions include a C18-sorbent/sample ratio of 2:1 (w/w) [total mixture weight = 100 mg] and 10 min of static extraction with 5 mL of 80% ethanol. The optimized MSPD extraction method was satisfactorily validated for all target flavonoids from both CBS and TBS. The validated method was also more effective and efficient compared to ultrasound- and homogenate-assisted extraction techniques. The overall results show that the MSPD extraction method developed in this study is a simple, effective, and efficient technique for the HPLC analysis of flavonoids in CBS and TBS. Highlights: MSPD extraction of flavonoids in buckwheat sprouts for HPLC was studied. Parameters affecting MSPD extraction efficiency were optimized. A simple, effective, efficient, and validated MSPD extraction method was developed.